A Recursive IndetermTree Soft Set (RIT-Soft Set) for Dynamic and Uncertain Performance Evaluation in College Competitive Sports, - Hai Yang; Cuijuan Lin (Neutrosophic Sets and Systems)
This paper introduces the Recursive IndetermTree Soft Set (RIT-Soft Set), a novel extension of Soft Set Theory designed for performance evaluation in dynamic and uncertain environments. Unlike conventional models, RIT-Soft Set incorporates recursive logic and supports hierarchical structures with embedded indeterminacy, allowing flexible representation of interdependent and evolving attributes. The model is particularly useful in domains where performance is context-dependent, and data may be incomplete or ambiguous such as universitylevel competitive sports. RIT-Soft Set enables recursive feedback within attribute trees, permitting deeper insight into athlete performance by allowing low-level data to influence higher-level assessments dynamically. A case study on a collegiate football team illustrates the practical application of the model, demonstrating how it can effectively manage multi-level evaluations involving physical, tactical, and psychological dimensions. The results show that the RIT-Soft Set provides greater interpretability and adaptability compared to flat or deterministic models. This framework opens avenues for developing decision-support systems that reflect real-world complexity and uncertainty, with potential for application beyond sports, in areas such as behavioral analysis and adaptive learning environments.